Content and language integrated learning in technical and Professional Education - Almeida, Juliana Monteiro dos Santos (2024)
This paper addresses the integration between English teaching as an Additional Language (EAL) and Technical and Professional Education (TPE), using CLIL (Content and Language Integrated Learning) approach. Based on qualitative research, the study identifies challenges in understanding technical terms in papers in English and proposes strategies to overcome them, using Google Scholar tools. These strategies were shared through a workshop to identify and comprehend technical terms, emphasizing Terminology and specialized vocabulary. The results reveal the importance of reading skill in English for students and highlight the effectiveness of CLIL in integrating content and language, promoting meaningful learning and preparing students for professional world.